Pembatalan Perjanjian Pengikatan Jual Beli Hak Milik Atas Tanah - Sri Antari, Ni Luh Yunik (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018), 2018)
The agreement on binding sale and purchase of land rights often experiences obstacles in practice. issues related to the agreement can result in the agreement being canceled. Cancellation of the agreement certainly causes losses to the parties so that there needs to be a protection due to the cancellation of the agreement. This writing aims to be able to know and analyze more deeply related to the legal consequences of the cancellation of the sale and purchase agreement on land rights and legal protection that can be granted in the cancellation of the agreement. This study uses a type of normative research. Moving on from the norm vacuum related to the cancellation of the sale and purchase agreement. So that it can be seen from the results of research related to the cancellation of the sale and purchase agreement that has been made can lead to legal consequences and agreements that have previously been made invalid or in other words the agreement ends and the parties are no longer bound as long as necessary as set in Article 1266 and 1267 Civil Code. Furthermore, the related parties will be fined for delays calculated every day. For the parties the legal protection that should be given is the condition of being returned as before before the binding agreement on the sale and purchase of land, money previously paid by the buyer to the seller, must be returned by the seller to the buyer and vice versa due to the cancellation of the agreement. return his property.